DEVELOPMENT AND IN VITRO EVALUATION OF PHYTOSOMES OF ELLAGIC ACID - B, JEEVANA JYOTHI; K, RAMYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The main objective of the present work is to enhance the bioavailability of ellagic acid (EA) by increasing its dissolution there by allowing for the exploitation of its therapeutic effects. Methods: Phytosomes containing EA were prepared by anti-solvent precipitation method. The prepared phytosomes were evaluated for drug entrapment efficiency, in vitro drug release, and drug excipient interaction studies. Results: Formulation F2 containing EA and soya lecithin in the ratio (1:2) showed highest percentage of drug release as 85.40% in 60 min and 95.86% in 120 min. The drug entrapment efficiency values were satisfactory. There were no interactions between the drug and the excipients used in its preparation according to Fourier-transform infrared spectra of pure EA and EA phytosomes. Conclusion: Phytosomes of EA were successfully produced by anti-solvent precipitation method and the percentage drug entrapment efficiency was satisfactory in almost all formulations. Formulation F2 exhibited highest percent of drug release as 85.40% in 60 min and 95.86% in 120 min to possess optimum bioavailability.